Central Corneal Thickness Reproducibility among Ten Different Instruments. Issue 11 (November 2016) - Pierro, Luisa; Iuliano, Lorenzo; Gagliardi, Marco; Ambrosi, Alessandro; Rama, Paolo; Bandello, Francesco
ABSTRACT: Purpose: To assess agreement between one ultrasonic (US) and nine optical instruments for the measurement of central corneal thickness (CCT), and to evaluate intra- and inter-operator reproducibility. Methods: In this observational cross-sectional study, two masked operators measured CCT thickness twice in 28 healthy eyes. We used seven spectral-domain optical coherence tomography (SD-OCT) devices, one time-domain OCT, one Scheimpflug camera, and one US-based instrument. Inter- and intra-operator reproducibility was evaluated by intraclass correlation coefficient (ICC), coefficient of variation (CV), and Bland-Altman test analysis. Instrument-to-instrument reproducibility was determined by ANOVA for repeated measurements. We also tested how the devices disagreed regarding systemic bias and random error using a structural equation model. Results: Mean CCT of all instruments ranged from 536 ± 42 μm to 577 ± 40 μm. An instrument-to-instrument correlation test showed high values among the 10 investigated devices (correlation coefficient range 0.852–0.995; p values <0.0001 in all cases). The highest correlation coefficient values were registered between 3D OCT-2000 Topcon—Spectral OCT/SLO Opko (0.995) and Cirrus HD-OCT Zeiss—RS-3000 Nidek (0.995), whereas the lowest were seen between SS-1000 CASIA and Spectral OCT/SLO Opko (0.852). ICC and CV showed excellent inter- and intra-operator reproducibility for all optic-based devices, except for the US-based device. Bland-Altman analysis demonstrated low mean biases between operators. Conclusions: Despite highlighting good intra- and inter-operator reproducibility, we found that a scale bias between instruments might interfere with thorough CCT monitoring. We suggest that optimal monitoring is achieved with the same operator and the same device. Abstract : Supplemental digital content is available in the text.